The Journal Rankings of Central Banks - Emanuel Kohlscheen (Swiss National Bank, Study Center Gerzensee, 2011)
This paper analyzes the citation patterns of the central banks of the 15 largest monetary areas of the world that had an active working paper series in 2010. It proceeds to construct a novel journal ranking that is more suited for monetary authorities than the academic journal rankings currently in vogue. We report individual country rankings as well as the global rankings. While important regional differences emerge, the Journal of Monetary Economics, the American Economic Review, the Journal of Money, Credit and Banking and the Journal of Finance stand out as the top outlets in the global ranking. Sweden's Riksbanken appears to be the monetary authority that is most finely tuned with academia, followed by the European Central Bank.
Keywords: A11; E50; E58; 330; central banks; citations; economic journals; rankings; Zentralbank; Bibliometrie; Fachzeitschrift